2004
DOI: 10.1007/s10072-004-0229-0
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effectiveness of steroid injections and splinting in mild and moderate carpal tunnel syndrome

Abstract: To evaluate the long-term efficacy of non-surgical treatment methods for mild and moderate carpal tunnel syndrome, 120 patients with clinical symptoms and electrophysiologic evidence were included in a prospective, randomized and blinded trial: 60 patients were instructed to wear splints every night, 30 received injections of betamethasone 4 cm proximal to the carpal tunnel, and 30 received injections distal to the carpal tunnel. After approximately 1 year (mean, 11 months; range, 9-14), 108 patients were avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 10 publications
5
37
0
6
Order By: Relevance
“…There are many studies regarding splint application on neutral and extension. (0-20°) [5,9,[20][21][22][23][24]. It is reported that in splint application the optimal angle on which the median nerve is most comfortable can vary for each individual [16].…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies regarding splint application on neutral and extension. (0-20°) [5,9,[20][21][22][23][24]. It is reported that in splint application the optimal angle on which the median nerve is most comfortable can vary for each individual [16].…”
Section: Introductionmentioning
confidence: 99%
“…The neutral position of the wrist, reduce the pressure on the median nerve in the carpal tunnel and splints are designed to hold the wrist in the neutral position [8,22]. The efficacy of wrist splinting has been variably demonstrated in several studies [7,[23][24][25]. In a randomized case-control trial by Premoselli et al, it is reported that splinting therapy improved symptoms and electrophysiological parameters in CTS patients [23].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our study, Kruger et al reported significant improvement in signs and symptoms of CTS and distal sensory latency in 67% of 105 patients with CTS and also reported that it is possible to get a positive result if the treatment starts within the first three months of the disease [7]. Also in a prospective, randomized, and blinded trial with 1-year follow-up, it is reported that splinting therapy improved symptoms, motor, and sensorial conduction velocities when the splints were worn almost every night [25]. Usually, the diagnosis of carpal tunnel syndrome is made primarily by clinical examination and the patient's history of symptoms, though it is necessary to confirm the diagnosis with the use of electrodiagnostic nerve testing.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in the other trial of 120 patients by Sevim et al comparing steroid injection and splinting, only splinting provided symptomatic relief while injections of steroids were ineffective at 1-year follow-up. 26 However, the conclusions of these two studies are limited either by the small sample size or the lack of a validated outcome measure.…”
Section: Discussionmentioning
confidence: 99%